Diagnosis and treatment of autoimmune pancreatitis types 1 and 2. Issue 10 (22nd July 2014) - Fritz, S; Bergmann, F; Grenacher, L; Sgroi, M; Hinz, U; Hackert, T; Büchler, M W; Werner, J
Abstract: Background: Autoimmune pancreatitis (AIP) is characterized by diffuse or focal swelling of the pancreas. AIP has been divided into types 1 and 2. The aim of the study was to evaluate and compare the clinicopathological characteristics, therapy and outcome of patients with AIP. Methods: The medical records of patients diagnosed with AIP between January 2003 and July 2011 were reviewed. Characteristics of patients with AIP types 1 and 2 were compared with those of patients with pancreatic ductal adenocarcinoma (PDAC). Results: AIP was classified as type 1 in 40 patients and type 2 in 32 according to the HISORt (Histology, Imaging, Serology, Other organ involvement, Response to therapy) criteria. Patients with histologically confirmed AIP type 2 were younger than those with type 1 ( P = 0·005). Some 30 of 32 patients with AIP type 2 were found to have a localized tumour-like pancreatic mass and underwent pancreatectomy, compared with only 16 of 40 with type 1 ( P < 0·001). Three of 25 patients with AIP type 2 presented with raised serum levels of IgG4 compared with 21 of 38 with type 1 ( P < 0·001). There was no difference in symptoms and involvement of other organs between AIP types 1 and 2. Presentation with weight loss was more common among patients with PDAC than those with AIP, but there was no difference in pain or jaundice between the groups. Raised serum carbohydrate antigen 19-9 levels were more prevalent in patients with PDAC. Conclusion: Patients with AIP type 2 frequently present with abdominal pain and a tumour-like mass. Differentiating AIP from PDAC is difficult, so making the clinical decision regarding operative versus conservative management is challenging. Abstract : Type 2 mimics pancreatic adenocarcinoma